Dhikr therapy for a patient at risk of violent behavior: A psychiatric nursing case study - Nural Wafinur; Mamnuah Mamnuah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Risk of violent behaviour is a common behavioural problem among patients with schizophrenia and is characterized by an increased potential to cause physical or psychological harm to oneself, others, or the surrounding environment. In addition to pharmacological treatment, psychoreligious interventions such as dhikr may help patients regulate emotions and improve self-control. Purpose: To describe the implementation of psychoreligious therapy using dhikr in reducing the signs and symptoms of risk of violent behaviour in a patient with schizophrenia. Method: A qualitative descriptive study using a single-patient case study design was conducted at Wisma Srikandi, Grhasia Mental Hospital, Yogyakarta. The nursing diagnosis was established based on the Indonesian Nursing Diagnosis Standards (INDS), and psychoreligious therapy using dhikr was implemented as part of nursing care for five consecutive days, with each session lasting 10–15 minutes. Patient progress was evaluated through daily clinical observation using the Indonesian Nursing Outcomes Standards (SLKI). Results: After five days of intervention, the patient demonstrated a reduction in the frequency of the signs and symptoms associated with the risk of violent behaviour. Improvements were observed in emotional control, anger management, willingness to follow therapeutic recommendations, and the patient's ability to control aggressive impulses based on daily nursing outcome assessments. Conclusion: Psychoreligious therapy using dhikr may contribute to improvements in the clinical manifestations of risk of violent behaviour when provided as an adjunct to standard psychiatric nursing care. Because the findings are based on a single case, they should be interpreted cautiously and cannot be generalized to broader patient populations. Keywords: Dhikr; Psychoreligious Therapy; Risk of Violent Behaviour; Schizophrenia.